Kantin Politeknik Dilihat Dari Perilaku Mahasiswa Administrasi Niaga Sebagai Konsumen (Studi Kasus Pada Mahasiswa Administrasi Niaga Politeknik Negeri Jakarta) - Azwar Azwar; Anwar Mustofa (Politeknik Negeri Jakarta, 2019)
This study aims to determine the opinions of bussines Administration students about the Jakarta State Polytechnic canteen, both the kantin bawah (kawah) and the kantin teknik (kantek). Canteen is one of the places of interest by students to meet their physical needs. In relation to fulfilling the needs of these business Administration students, what can be served in the kantin bawah or the kantin teknik is what they need and can not be what they expect either the food offered or the drinks served or other factors they get in canteen. The data analysis method used is qualitative and quantitative analysis or combination analysis. Qualitative is done by describing the results of quantitative analysis, while quantitative analysis using the formula of the attitude indeks. Data collection uses questionnaires given to respondents to obtain primary data and literature studies to obtain secondary data. The results of this study indicate that the biggest attitude index is the technical canteen which is 3.08 and for the lower canteen is 2.73. This reflects that the canteen most favored by business administration students of the Jakarta State Polytechnic is a kantin teknik.